Cancer cell membrane cloaking nanoparticles for targeted co-delivery of doxorubicin and PD-L1 siRNA - Mushi Chen; Ming Chen; Jiantai He (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Nanoparticles coated with cell membranes have been garnering growing attention due to their homologous binding capability of membrane molecules and consequent self-recognition by their source cells. In the present study, we report on the construction of doxorubicin and PD-L1 siRNA-loaded PLGA nanoparticles and their biological functionalization by cancer cell-derived membrane cloaking. The resulting cancer cell membrane-coated nanoparticles (CCMNPs) presented a core-shell nanostructure with highly specific self-recognition affinity to the homotypic cells, which can be attributed to the transference of cell adhesion molecules with homotypic binding properties. These findings facilitate the application of this bioinspired strategy for effective delivery of siRNA and precise tumour therapy.